Giant ovarian fibrosarcoma: A rare case report - Pratibha Kumari; Satya Kumari; Jyotsna Rani; Kavya Abhilashi; Kshiti Atreya; Deepak Kumar; Vijayanand Choudhary; Sangeeta Pankaj; Supriya Jaiswal (Wolters Kluwer -Medknow Publications, 2022)
Sex cord-stromal tumors are very rare ovarian tumors. Primary ovarian fibrosarcomas are a very rare type of sex cord-stromal tumors. They arise from superficial or deep connective tissues of fascia, tendon, periosteum, and scar. They can grow either slowly or rapidly forming a giant abdominal mass similar to epithelial tumors of the ovary. Fibrosarcomas are difficult to diagnose preoperatively. Tumor marker and radiological techniques play a trivial role in preoperative diagnosis of this rare variety of sex cord-stromal tumor. Often final diagnosis is made on histopathological and immunohistochemistry reporting. Histopathological features such as high mitotic count, nuclear atypia, and herringbone pattern arrangement of spindle cells confirm a diagnosis of malignant fibrosarcoma. Ki-67 index is considered a prognostic factor for fibromatous lesions of the ovary showing aggressive nature of tumor. We report a rare case of giant ovarian fibrosarcoma in a 40-year-old woman whose diagnosis was made histopathologically due to rarity of tumor.